A Case of a Rapidly Progressive Small Bowel Lymphoma with High Ki-67 Expression - Jiyeon Yoo; Hee Jun Kang; Hyungkeun Kim; Sujeong Han; Seung Hyun Oh; Sung Hoon Jung; Jung Hwan Oh; Eun Jung Jeon (Yong Chan Lee, 2017)
Primary intestinal lymphoma is a rare disease. It accounts for approximately 1∼4% of gastrointestinal malignancy. Extranodal lymphoma of the intestine mainly arises from B cells. Diffuse large B-cell lymphoma is the most common type of the disease. Approximately 40% of intestinal lymphoma can be cured, while 60% have varied disease progression. Ki-67 proliferation has been recently used as an index of cell growth to predict the progression of the disease. Reported herein is a case of a rapidly progressive small bowel diffuse large B-cell lymphoma in a 51-year-old man with a high Ki-67 expression level. He visited the emergency department because of hematochezia. Abdominal computed tomography revealed distal small bowel segmental wall thickening. He underwent operation due to spontaneous small bowel perforation. The result of the pathological examination of the resected specimen was compatible with diffuse large B-cell lymphoma. The Ki-67 index within 5 months was 90%.